2016
DOI: 10.1016/j.jcin.2015.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Permanent Pacemaker Implantations and New-Onset Conduction Abnormalities With the SAPIEN 3 Balloon-Expandable Transcatheter Heart Valve

Abstract: Implantation depth and prosthesis oversizing were associated with a higher rate of new CA or PPI using the SAPIEN 3. Thus, avoidance of deep implantation and extreme oversizing may reduce these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 31 publications
8
105
1
2
Order By: Relevance
“…A recent report identified implantation depth and oversizing as independent predictors of new permanent pacemaker implantation with SAPIEN 3, suggesting a potential procedural opportunity to reduce the rate. 14 The small increase in stroke between 30 days and 1 year is not surprising in this elderly population with multiple risk factors for stroke, including atrial fibrillation in >40% of patients. Studies, including GALILEO (Global Study Comparing a Rivaroxaban-Based Antithrombotic Strategy to an Anti-Platelet-Based Strategy After Transcatheter Aortic Valve Replacement; Clinicaltrials.gov NCT02556203), comparing antiplatelet and anticoagulation strategies aimed at reducing post-TAVR thromboembolic events are underway.…”
mentioning
confidence: 96%
“…A recent report identified implantation depth and oversizing as independent predictors of new permanent pacemaker implantation with SAPIEN 3, suggesting a potential procedural opportunity to reduce the rate. 14 The small increase in stroke between 30 days and 1 year is not surprising in this elderly population with multiple risk factors for stroke, including atrial fibrillation in >40% of patients. Studies, including GALILEO (Global Study Comparing a Rivaroxaban-Based Antithrombotic Strategy to an Anti-Platelet-Based Strategy After Transcatheter Aortic Valve Replacement; Clinicaltrials.gov NCT02556203), comparing antiplatelet and anticoagulation strategies aimed at reducing post-TAVR thromboembolic events are underway.…”
mentioning
confidence: 96%
“…The overall rates of permanent pacemaker implantation after TAVR were around 17%, versus 5% with SAVR. 66,67 The need for a new permanent pacemaker in the Partner A cohort was not significantly different at 30 days (3.8% vs 3.6%), 1 year (5.7% vs 5%) and 5 years (9.7% vs 9.1%) for patients undergoing TAVR versus SAVR, respectively. Siontis and colleagues 66 suggested that male sex, baseline conduction disturbances, and intraprocedural atrioventricular block had roles as predictors of permanent pacemaker implantation after TAVR.…”
Section: Technical Sequelae Of Tavrmentioning
confidence: 93%
“…However, the rates of permanent pacemaker implantation and conduction abnormalities were also found to be higher with the new Edwards Sapien 3 system because of prosthesis oversizing and the depth of the implantation. 67 Other Sequelae. Paravalvular leak after TAVR is a frequent occurrence that is associated with increased mortality rates.…”
Section: Technical Sequelae Of Tavrmentioning
confidence: 99%
“…The continuous development of TAVI procedures has decreased the incidence of various complications regarding TAVI. This includes vascular complication, annulus rupture, paravalvular regurgitation, stroke, and conduction disturbance . Coronary artery obstruction still remains a critical concern of this procedure .…”
Section: Discussionmentioning
confidence: 99%